Sensitivity and specificity of bispectral index for classification of overt hepatic encephalopathy: a multicentre, observer blinded, validation study. Issue 1 (14th August 2007) - Dahaba, A A; Worm, H C; Zhu, S M; Bao, F P; Salah, A; Zakaria, S; Bornemann, H; Stadlbauer, V; Rehak, P H; Metzler, H; Stauber, R E
Abstract : Background: The severity of hepatic encephalopathy is currently graded clinically using West Haven criteria and psychometric tests. Objective: To assess the discriminative power of the bispectral index (BIS) monitor to classify the degree and progression of hepatic encephalopathy. Design: A consecutive, multicentre, observer blinded validation study. Setting: Medical University of Graz (Graz, Austria), Zhejiang University First Affiliated Hospital (Hang Zhou, China), and Cairo University (Cairo, Egypt). Patients: 28 consecutive patients with hepatic encephalopathy were first enrolled at Medical University of Graz as a test set. The estimated BIS cut off values were subsequently tested in a validation set of 31 patients at Zhejiang University First Affiliated Hospital and 26 patients at Cairo University; 18 patients were reassessed later in a longitudinal study. Fifteen of 85 patients (18%) were excluded from the final analysis (11 became too agitated with high electromyographic activity; four fell asleep during the recording). Results: Applying the Austrian BIS cut off values of 85, 70, and 55 for discriminating West Haven grades 1 to 4 yielded agreement between BIS classification and West Haven grades in 40 of the 46 validation patients (87%), and in 16 of the 18 follow up patients (89%). Mean (SD) BIS values differed significantly between patients with West Haven grade 1 (90.2 (2.5)), grade 2 (78.4 (6.6)), grade 3 (63.2 (4.8)), and grade 4 (45.4 (5.0)). Conclusions: BIS is a useful measure for grading and monitoring the degree of involvement of the central nervous system in patients with chronic liver disease.